Interstitial lung disease in a veterans affairs regional network; a retrospective cohort study - Bedoya, Armando; Pleasants, Roy A.; Boggan, Joel C.; Seaman, Danielle; Reihman, Anne; Howard, Lauren; Kundich, Robert; Welty-Wolf, Karen; Tighe, Robert M. (PloS one, 2021)
The epidemiology of Interstitial Lung Diseases (ILD) in the Veterans Health Administration (VHA) is presently unknown. Describe the incidence/prevalence, clinical characteristics, and outcomes of ILD patients within the Veteran's Administration Mid-Atlantic Health Care Network (VISN6). A multi-center retrospective cohort study was performed of veterans receiving hospital or outpatient ILD care from January 1, 2008 to December 31st, 2015 in six VISN6 facilities. Patients were identified by at least one visit encounter with a 515, 516, or other ILD ICD-9 code. Demographic and clinical characteristics were summarized using median, 25th and 75th percentile for continuous variables and count/percentage for categorical variables. Characteristics and incidence/prevalence rates were summarized, and stratified by ILD ICD-9 code. Kaplan Meier curves were generated to define overall survival. 3293 subjects met the inclusion criteria. 879 subjects (26%) had no evidence of ILD following manual medical record review. Overall estimated prevalence in verified ILD subjects was 256 per 100,000 people with a mean incidence across the years of 70 per 100,000 person-years (0.07%). The prevalence and mean incidence when focusing on people with an ILD diagnostic code who had a HRCT scan or a bronchoscopic or surgical lung biopsy was 237 per 100,000 people (0.237%) and 63 per 100,000 person-years respectively (0.063%). The median survival was 76.9 months for 515 codes, 103.4 months for 516 codes, and 83.6 months for 516.31. This retrospective cohort study defines high ILD incidence/prevalence within the VA. Therefore, ILD is an important VA health concern.